Does 'Best Practice' in Setting Executive Pay in the UK Encourage 'Good' Behaviour? - Bender, Ruth; Moir, Lance (Springer Science Business Media, 2006)
We examine how UK listed companies set executive pay, reviewing the implications of following best practice in corporate governance and examining how this can conflict with what shareholders and other stakeholders might perceive as good behaviour. We do this by considering current governance regulation in the light of interviews with protagonists in the debate, setting out the dilemmas faced by remuneration-setters, and showing how the processes they follow can lead to ethical conflicts. Current ?best? practice governing executive pay includes the use of market benchmarks to determine salary and bonus levels, significant levels of performance-related pay, the desire for executives to hold equity in their companies, the disclosure of total shareholder return compared to an index, and a perceived need for conformity, in order to grant legitimacy to policies. Whilst each of these may in some circumstances lead to good practice, each has the potential to cause dysfunctional behaviour in executives. Overall, we conclude that although best practice might drive good executive behaviour that coincides with the company?s and key stakeholders? objectives, there are many reasons why it should not.
Keywords: compensation; ethics; executive; governance; remuneration; stakeholder